Prospects of involving local communities in Joint Forest Management in Oyo State, Nigeria (2007)
The study assessed the prospects of community participation in Joint Forest Management (JFM) in Oyo State. This is against the backdrop of the State's forestry department perfecting strategies and logistics for community participation in forestry activities in the State. Primary data were sourced through open-ended and structured questionnaires, while secondary data were obtained from the state's forestry publications, records and reports. Additional information was sourced through Focus Group Discussion (FGD). A multi-stage random sampling technique was used for questionnaire administration. A forest reserve was first selected from each of the four (4) forestry administrative zones in the State. In each of these reserves, two communities were randomly selected to elicit information from members of local communities living within and around the reserve. A total of eight communities were involved in the study. One-hundred and sixty (160) questionnaires were administered on the inhabitants. Data generated were analyzed using descriptive tools and appropriate inferential test statistics. The study identified Taungya farming as a means of enlisting communal supports in the management of reserve and a way of regenerating forest stand. However, this practice is viewed by local communities as grossly inadequate. Besides, lack of fund, and non availability of planting stocks on most occasion are major constraints against the system. Further, Chi-square test statistics reveal a significant (Pr < 0.05) level of dependence of willingness of respondents to participate in JFM on their socio-economic background. Also, a significant level of dependence was established between willingness to participate in JFM and respondent's consent to communal involvement in forest in management (X2=70.49, df = 2, Pr = 0.01) as well as index of involvement of respondent in forest management (X2 = 70.49, df = 2, Pr = 0.01). The regression model further indicates a relatively high positive relationship (df =152, R=0.517, R2 = 0.268) between demographic/socio-economic features of respondents and willingness to participate in Joint Forest Management with the State. Thus, although socio-economic characteristics of respondents impacts participation, implementation of JFM in Oyo State is imperative and will need to build on present management Structure to succeed.